Percentage of Neutrophyl Lymphocyte Ratio and Glycated Hemoglobin in Type 2 Diabetes Mellitus Patients at Waled Hospital - Adilah, Zahra Ul; Silvia, Indriani; Amaliyah , Nihayatul (Al-Makki Publisher, 2025)
Diabetes mellitus (DM) is one of the leading causes of death in the world. The number of DM patients is increasing every year so it is necessary to treat and prevent it with an HbA1c laboratory examination as an establishment of the diagnosis of DM and a supporting examination using neutrophil lymphocyte ratio (NLR) as a complications marker from hyperglycemia. This study was conducted to determine the percentage of neutrophil lymphocyte ratio and glycated haemoglobin in type-2 diabetes mellitus patients at Waled Regional General Hospital. This study is an observational descriptive study using total sampling. The population in this study is type-2 DM patients aged 19-65 years with 39 samples. Type-2 DM patients who underwent NLR and HbA1c examinations showed that 16 (41%) male and 23 (59%) female patients, the highest age group was 17 (43.6%) in the age group of 46-55 years. The percentage of NLR values in this study was the normal range: 1-2 (53.8%) and the percentage of HbA1c values in this study was poor: >8 mmol/mol (48.7%). The presentation of NLR values in this study was obtained to be normal and increase HbA1c levels percentage.